2020
DOI: 10.1080/23802359.2020.1773333
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the complete chloroplast genome of Tulipa iliensis (Liliaceae)

Abstract: The chloroplast genome and evolutionary relationship analysis of Tulipa gesneriana L. could provide fundamental genetic reference for its molecular breeding and biological research. The complete chloroplast genome of Tulipa iliensis was sequenced and reported here. Its chloroplast genome was 151,744 bp in length, containing a pair of inverted repeated regions (26,354 bp) which were separated by a large single copy region of 81,794 bp, and a small single copy region of 17,242 bp. Moreover, a total of 133 functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…In the process of marker selection, we compared existing complete chloroplast genomes of Tulipa species available in public databases to identify suitable markers [ 30 , 31 ]. The markers used in our study were selected based on their demonstrated utility in phylogenetic studies and their potential for reliable amplification and sequencing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of marker selection, we compared existing complete chloroplast genomes of Tulipa species available in public databases to identify suitable markers [ 30 , 31 ]. The markers used in our study were selected based on their demonstrated utility in phylogenetic studies and their potential for reliable amplification and sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, numerous studies have investigated the genetic diversity of the Liliaceae family and the genus Tulipa , using various genetic barcoding markers and sequencing techniques [ 1 , 5 , 29 , 30 , 31 , 32 , 33 , 34 ]. The generations and analysis of expressed sequence tags in the extremely large genomes of Tulipa were published in 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its characteristics of solitary terminal flowers, large and brightly colored petals, strong adaptability, and short growth cycle, Tulipa iliensis possesses high ornamental value and can provide abundant parental materials for breeding purposes. In recent years, research on Tulipa iliensis has mainly focused on genetic diversity [23][24][25][26], seed germination characteristics [27][28][29][30], dormant habits [31], phenological characteristics [32][33][34], chloroplast genome characteristics and other related areas [35]. However, there is currently no research on the distribution trend of Tulipa iliensis under climate change conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several chloroplast genomes of Tulips have been published, but the cp genome of T. gesneriana is lacking (Ju et al. 2020 ; Li et al. 2021 ).…”
mentioning
confidence: 99%